Love on the second read - De Leon, Mica (Penguin Random House SEA, 2023)
Emma Morales, tenacious romance book editor and proud cat lady, knows romance, but love? Nope. Thank you very much. Enter nerdy science fiction and fantasy editor Kip Alegre, who quotes JRR Tolkien for breakfast and knows heartbreak all too well. When Emma gets a career-changing sci-fi romance manuscript which may just save their publishing house from folding, she knows she must work with Kip if she wants to succeed. Sounds simple enough, right? But when the well-meaning meddling best friends, an obsessive ex-boyfriend, and a beautiful ex-fiancée get into the picture, the job doesn’t seem so simple anymore. What starts out as a friendly-flirty-literary smackdown between Emma and Kip by quoting authors from Emily Henry to Brandon Sanderson grows into something deeper than either of them had signed up for. The deal was to edit the book, not their lives.-- Back cover